The Application of Ethnography in the Study of Space and Place: A Case Study of Women's Movement in the Tehran Bazaar. - Mina Bidar; Abbas Varij Kazemi (طراحی و برنامه ریزی در معماری و شهرسازی)
This article addresses the methodological shortcomings in the study of urban spaces in Iran and highlights the usefulness of ethnographic research in motion for urban and urban design studies based on fieldwork on gender relations in the physical space of the Tehran Bazaar. It also examines the innovative approaches employed by the authors in applying this method. The ethnographic research in motion concerning the chosen case study provides insights into the formation and remembrance of a sense of place during movement in the bazaar, critical interventions in space through women's navigation and crossing of gendered boundaries within the market, the creation of new spaces, as well as the rhythm of women's presence in the space, which encompasses both long movements and short stops, and their specific decision-making processes for navigating the unique physicality of the market. The results of this article demonstrate that the use of ethnography in motion, particularly in movement-based urban space studies, is valuable. In addition to providing analyses of people's emotions and experiences at different points in their presence within the space, it offers a macro-level perspective on people's trajectories and locations in the space, providing researchers with a unique set of data on the formation of perceived space and enabling specific analytical capabilities not easily accessible through other methods. Ethnography in motion can contribute to a deeper understanding of the gendering of the environment, the inclusivity of the urban environment, and the overall production and appropriation of space by different groups and segments of society, showcasing the critical engagement of groups (in this case, women) with the dominant spatial discourse. When the knowledge gained through this approach intersects with the qualitative qualities of the analyzed environment, it can be highly beneficial in designing urban spaces that cater to the diverse segments of society.